2016
DOI: 10.1177/1932296816658746
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Patterns and the Cost of Antihyperglycemic Drugs in Patients With Type 2 Diabetes Mellitus in Germany

Abstract: Diabetes is a chronic disease which affects around 8.3% of the worldwide population. 1,2 It is estimated that 1 in every 13 persons in Germany has diabetes. 3 Type 2 diabetes mellitus (T2DM) is found in 90% of individuals with diabetes. 4 The current annual German cost associated with T2DM of approximately €11.8 billion in 2010 will exceed €21 billion in 2040, underscoring the major burden of diabetes in this country. 5 Reduction of blood glucose levels in T2DM patients is important since it can prevent microv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 18 publications
2
29
0
Order By: Relevance
“…Similar trends in antidiabetic use have also been observed in other countries, but with smaller changes and variation in use for specific antidiabetic drugs . In 2017, the use of sulphonylureas and GLP‐1RAs each accounted for 8% of the total antidiabetic drug use in Denmark.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Similar trends in antidiabetic use have also been observed in other countries, but with smaller changes and variation in use for specific antidiabetic drugs . In 2017, the use of sulphonylureas and GLP‐1RAs each accounted for 8% of the total antidiabetic drug use in Denmark.…”
Section: Discussionsupporting
confidence: 61%
“…[4][5][6]16 Similar trends in antidiabetic use have also been observed in other countries, but with smaller changes and variation in use for specific antidiabetic drugs. 9,17,18 In 2017, the use of sulphonylureas and GLP- speculated that the blood glucose-lowering effects of these drugs simply seem to be outweighed by their side effects.…”
Section: Discussionmentioning
confidence: 99%
“…One French study also reported higher costs for younger patients (€15299.46 for patients aged < 60 years vs. €9728.25 for patients aged ≥ 75 years) (64). Similar heterogeneous results were found for sex: higher costs for men (54) and also higher costs for women (43).…”
Section: Cost Drivers In France and Germanymentioning
confidence: 61%
“…Complications or comorbidities contribute to higher overall direct healthcare costs and direct costs for diabetes treatment, respectively (44,54). For Germany, the most expensive diabetes-related complications are end-stage renal disease (occurrence €32738.14, one-year follow-up €23629.17), amputations (occurrence €20512.96, one-year follow-up €12818.02) and fatal ischaemic heart disease (occurrence €19874.15) (44).…”
Section: Cost Drivers In France and Germanymentioning
confidence: 99%
“…The quality of these data is assessed on a regular basis, and it was shown by Becher and colleagues that the Disease Analyzer database is representative of German practices [14]. Finally, several diabetes studies have already been conducted using this database [15][16][17][18].…”
Section: Databasementioning
confidence: 99%